2015
DOI: 10.5588/ijtld.14.0648
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors for tuberculous infection following exposure at a homeless shelter

Abstract: Birthplace and duration of exposure were significant risk factors for tuberculous infection, underscoring the importance of this information when prioritizing contact investigations after TB exposure in congregate settings. We recommend that public health agencies work with homeless shelters to ensure that clients' attendance records contain the necessary information to facilitate contact tracing during public health TB investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
0
8
0
3
Order By: Relevance
“…Contacts of the patient are the very susceptible to infection [16] so, education of patient family for proper home ventilation, avoidance of direct exposure to patients' air droplets on coughing and disinfection methods is essential [17].…”
Section: Discussionmentioning
confidence: 99%
“…Contacts of the patient are the very susceptible to infection [16] so, education of patient family for proper home ventilation, avoidance of direct exposure to patients' air droplets on coughing and disinfection methods is essential [17].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent risk factors, for both groups, identified in this study are similar to the ones described in the literature. 10,[19][20][21][22][23][24][25][26][27][28][29]31,35 In patients with PTB, being a smoker was associated with an increased risk to acquire TB. In many studies active and passive smoking was found to be associated with TB infection/ disease, severity of disease, necessity of retreatment and mortality.…”
Section: -7mentioning
confidence: 99%
“…Accordingly, they should be adequately monitored to achieve earlier diagnoses of TB. 31,34,35,48 Immunosuppression is another risk factor to take in account. Infection by HIV, use of immunosuppressive therapy and presence of cancer, all are related with an increased development of TB.…”
Section: -7mentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of readily available information about a person's susceptibility, duration of exposure to an infectious person has been used to prioritize contacts. Although this benchmark for exposure is linked to risk for transmission (7,8), the measure is not well defined.…”
mentioning
confidence: 99%